Thesauri and Formal Classifications: Terminologies for People and Machines - Rector, A. L. (Methods of Information in Medicine, 1998)
Terminologies are now software. They are key components of the integration of electronic patient records, decision support systems and information retrieval systems. To be used as software, the different types of content in traditional terminologies must be separated, which we term here: conceptual, linguistic, inferential and pragmatic. The conceptual knowledge at the heart of the terminology needs to be expressed formally in order to provide a dependable framework for the other types of knowledge. Information left implicit in most existing coding and classification systems must be made explicit. The test of the resulting terminologies is how well they support software for key functions: including data entry, information retrieval, mediation, indexing, and authoring.
Keywords: Terminologies; Software; Concept Representation